All-inorganic cesium lead iodide perovskite solar cells with stabilized efficiency beyond 15% - Kang Wang (Nature Portfolio, 2018)
Black phase cesium lead iodide perovskite is regarded as a promising candidate for solar cells, but it easily transits to undesired yellow phase. Herein, Wang et al. stabilized the black phase using molecular additives to achieve device efficiency beyond 15% with high light soaking stability.